USE OF CASE BASED LEARNING AS A TEACHING LEARNING METHOD IN UNDERGRADUATE PATHOLOGY TEACHING- OUR EXPERIENCE. - Jaison, Janice; Murgod, Priyanka; Kate, Prachi; Zope , Rajendra; Bhide, Smita; Gupta, Digant (Student's Journal of Health Research Africa, 2023)
Background The CBME Curriculum introduced by NMC is a subject based education. Newer components like alignment and integration provide an understanding of the interconnectedness between subjects and their application in patient care. Pathology bridges the basic sciences with the clinical sciences. Case Based Learning (CBL) is a pedagogical method in which the basic sciences are studied in relation to a case. It lays emphasis on the development of higher orders of cognition like interpretation and application rather than promoting learning by rote. Aims & Objectives The objectives of this study were to assess the effectiveness of CBL as a Teaching Learning (TL) method in Pathology and also to analyze the perceptions of Phase II MBBS students regarding this TL method. Settings & Design The study setting was the Department of Pathology. It was a prospective interventional study using qualitative and quantitative (mixed method) study design. All Phase II MBBS students were included in this study. 5 sessions of CBL were conducted with a pre and post-test. Statistical Analysis Used The statistical analysis of the Pre and Post test scores was done using a Two Tailed Wilcoxon Signed Rank Test. Feedback was taken using a 5-point Likert scale and percentages were used to analyze the feedback. Results A significant improvement (p <0.001) was noted in the mean post test scores. The CBL sessions helped arouse interest in the topic (91.9%) and improve clinicopathological corelation skills (91.2%). Conclusion CBL promotes clinical corelation skills and serves as an excellent platform for the implementation of integrated learning in Pathology. It is recommended that more topics should be taught using CBL mode of TL to make the learning experience more practical oriented.